Sunitinib Combined with Th1 Cytokines Potentiates Apoptosis in Human Breast Cancer Cells and Suppresses Tumor Growth in a Murine Model of HER-2pos Breast Cancer - Nirmala Ghimirey; Chase Steele; Brian J. Czerniecki; Gary K. Koski; Loral E. Showalter (International Journal of Breast Cancer)
Although immune-based therapies have made remarkable inroads in cancer treatment, they usually must be combined with standard treatment modalities, including cytotoxic drugs, to achieve maximal clinical benefits. As immunotherapies are further advanced and refined, considerable efforts will be required to identify combination therapies that will maximize clinical responses while simultaneously decreasing the unpleasant and sometimes life-threatening side effects of standard therapy. Over the last two decades, evidence has emerged that Th1 cytokines can play a central role in protective antitumor immunity and that combinations of Th1 cytokines can induce senescence and apoptosis in cancer cells. To explore the possibility of combining targeted drugs with Th1-polarizing vaccines, we undertook a study to examine the impact of combining Th1 cytokines with the relatively broad-spectrum receptor tyrosine kinase antagonist, sunitinib. We found that when a panel of five phenotypically diverse human breast cancer cell lines was subjected to treatment with sunitinib plus recombinant Th1 cytokines IFN-γ and TNF-α, synergistic effects were observed across a number of parameters including different aspects of apoptotic cell death. Interestingly, sunitinib was found to have a profoundly suppressive effect of T cell’s capacity to secrete IFN-γ, indicating that in vivo use of this drug may hinder robust Th1 responses. Nonetheless, this suppression was circumvented in a mouse model of HER-2pos breast disease by supplying recombinant interferon-gamma to achieve a combination therapy significantly more potent than either agent.